Oxygen reduction voltammetry on platinum macrodisk and screen-printed electrodes in ionic liquids: Reaction of the electrogenerated superoxide species with compounds used in the paste of Pt screen-printed electrodes? - Lee, J.; Murugappan, Krishnan; Arrigan, Damien; Silvester, Debbie (Pergamon, 2013)
Screen-printed electrodes (SPEs) are widely investigated as simple, three-electrode planar surfaces for electrochemical sensing applications, and may be ideal for gas sensing purposes when combined with non-volatile room temperature ionic liquids (RTILs). In this report the suitability of SPEs with RTIL solvents has been investigated for oxygen detection. Oxygen reduction has been studied on commercially available platinum SPEs in eight RTILs. Cyclic voltammetric wave shapes were found to be significantly different on Pt SPE surfaces compared to conventional solid Pt macroelectrodes, suggesting a possible reaction of the electrogenerated superoxide with the compounds that make up the ink/paste of the SPE surface. The only RTIL that did not show such drastically different voltammetry was one that contained a pyrrolidinium cation, suggesting a more chemically stable solvent environment compared to the other imidazolium and phosphonium cations studied. The analytical utility was then studied on four SPE surfaces (carbon, gold, platinum and silver) in two RTILs (one with a pyrrolidinium and one with an imidazolium cation) and linear responses were observed between current and % concentration in the range 10–100% O2. This suggests that SPEs may indeed be suitable for oxygen sensing in some RTILs, but significantly more pre-treatment of the surface is required to obtain reliable results. However, the reaction of superoxide with the SPE ink, together with a noticeable deterioration of the signal over time, suggests that this type of sensing platform may only be suitable for “single-use” oxygen sensing applications.